The effect of performance expectancy on behavioral intention: The mediating role of satisfaction - Yuliantie, Emil (Universitas Ahmad Dahlan, 2024)
Purpose-Current technological developments have penetrated various aspects of life, including financial transactions. Financial technology can make it easier for people to conduct different financial transactions. One proof of the development of financial technology is the presence of electronic wallets, such as e-wallets. Therefore, this study aims to analyze e-wallet user satisfaction as measured by performance expectations and mediated by satisfaction. Design/Methodology/Approach-The population of this study consisted of Dana e-wallet users in Yogyakarta, Indonesia. Then, the research sample was determined based on purposive sampling using specific criteria, and a sample size of 84 respondents was obtained. The research data was collected by distributing questionnaires online, which contained statement items from each variable using a Likert scale. Then, the analysis tool used to process the data is Smart PLS version 4. Findings- This study proves that performance expectancy has a positive but insignificant effect on behavioral intention, while the relationship between performance expectancy and satisfaction has a positive effect. Satisfaction is proven to positively affect behavioral intention and mediate the relationship between performance expectancy and behavioral intention. Research limitations/implications-This research is limited to only a small number of samples and only for e-wallet users in Yogyakarta, so the research results cannot be used to generalize the behavioral intentions of e-wallet users in other areas. In addition, this research only focuses on Dana e-wallet users, not on other general e-wallet users. Originality/value-E-wallet service provider companies can consider the factors analyzed in this study to improve their product services. That way, the level of consumer intention to use e-wallets is expected to increase.